Facebook assisted students' peer assessment in writing descriptive text - Syifa Salsabila (English, 2020)
The present study aims to investigate students’ responses toward peer assessment in students’ descriptive text writing assignments by using Facebook. The author built two research questions: (1) In what way does Facebook assist students in giving peer assessment on students’ descriptive text writing? and (2) What are the students’ responses toward these activities? The current study recruited seventeen students in tenth grade as the participants. Drawing on action research through interviews and observation data, qualitative findings show positive results, those are (1) the use of students’ peer assessment through Facebook had an impact on raising the students’ revised drafts, (2) the students expressed an optimistic response towards using Facebook for peer assessment, and (3) the students’ difficulties on peer assessment through Facebook, and (4) the students’ involvement during peer assessment activities on Facebook. Furthermore, the quantitative findings of the observation checklist show that the average percentage is 88.4% (15 students of the class were actively involved in the writing activities = very good). Therefore, this present study shows the provident of the importance of peer assessment through Facebook as an assessment method to help enhance learners’ English writing acquisition.